Collegiate Recovery Program (CRP): Student Needs and Employee Roles - Gueci, Nika (Building Healthy Academic Communities Journal, 2018)
Background: Research on Collegiate Recovery Programs (CRPs) is emerging. There is a need to examine aspects of CRPs to highlight program efficacy and best practices within local settings. Aim: As distinct cycles within a larger action research study, two small inquiries within a local university setting assessed: (1) how student members of the organization "Students for Recovery" defined their needs, and (2) how student employees of the CRP described their roles and success in their work. Methods: Semi-structured interviews examined students in recovery and student CRP employees. Results: Thematic analysis for each group produced two sets of qualitative results. Members of the student organization "Students for Recovery" described their needs as social support and safety, awareness and advocacy. Student employees of the CRP described their role as outreach and one-on-one support as well as strategic program planning. Instances of success were described as the departmental support, and their unique peer perspective. Conclusions: Two queries described needs of students in recovery and role descriptions of student CRP employees within a specific setting. Robust studies are needed to understand the impact of local CRP programs and can provide context to guide informed, responsive programming and best practices.